1988
DOI: 10.1128/jb.170.12.5607-5612.1988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a unique methyl-specific restriction system in Streptomyces avermitilis

Abstract: Streptomyces avermitilis contains a unique restriction system that restricts plasmid DNA containing N6-methyladenine or 5-methylcytosine. Shuttle vectors isolated from Escherichia coli RR1 or plasmids isolated from modification-proficient Streptomyces spp. cannot be directly introduced into S. avermitilis. This restriction barrier can be overcome by first transferring plasmids into Streptomyces lividans or a modification-deficient E. coli strain and then into S. avermitilis. The transformation frequency was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
113
0
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 38 publications
3
113
0
1
Order By: Relevance
“…We are currently determining the nature and cause of this novel type of modification. In terms of DNA metabolism, these two species have previously been compared with regard to their ability to restrict methylated DNA (MacNeil, 1988). This study indicated that while S. lividans has a weak methyl-specific restriction system that can slightly reduce transformation frequencies with A$-methyladenine-containing DNA, S.…”
Section: Dna Manipulations Streptomyces Plasmid Dna Isolation Wasmentioning
confidence: 99%
“…We are currently determining the nature and cause of this novel type of modification. In terms of DNA metabolism, these two species have previously been compared with regard to their ability to restrict methylated DNA (MacNeil, 1988). This study indicated that while S. lividans has a weak methyl-specific restriction system that can slightly reduce transformation frequencies with A$-methyladenine-containing DNA, S.…”
Section: Dna Manipulations Streptomyces Plasmid Dna Isolation Wasmentioning
confidence: 99%
“…The dam-13: :Tn9 allele present in GM2163 was transferred to the isogenic pEG409-containing strains EG1884 and EG1885 by transduction with Plvir (27) Table 3). The only other strain that has been reported to restrict DNA modified by either the Dam or the Dcm methylase is Streptomyces avermitilis (19). Finally, the transformation frequencies for four other strains (HD3, HD4, HD7, and HD567-56) were low regardless of the source of plasmid DNA (Table 3).…”
mentioning
confidence: 97%
“…The (16). B40 and B17 are actVII and actIV actinorhodin-biosynthetic pathway mutants, respectively, which also carry the markers hisAl uraAl strAl (7,23,25 (18). The gra, "fren," otc, and tcm ACP genes were obtained from pIJ5200 (26), pIJ5214 (2), pIJ5210 (24), and pELE37 (10) (19).…”
mentioning
confidence: 99%